The Gaia-ESO survey: a lithium depletion boundary age for NGC 2232. Issue 1 (12th May 2021) - Binks, A S; Jeffries, R D; Jackson, R J; Franciosini, E; Sacco, G G; Bayo, A; Magrini, L; Randich, S; Arancibia-Silva, J; Bergemann, M; Bragaglia, A; Gilmore, G; et al.
ABSTRACT: Astrometry and photometry from Gaia and spectroscopic data from the Gaia -ESO Survey (GES) are used to identify the lithium depletion boundary (LDB) in the young cluster NGC 2232. A specialized spectral line analysis procedure was used to recover the signature of undepleted lithium in very low luminosity cluster members. An age of 38 ± 3 Myr is inferred by comparing the LDB location in absolute colour−magnitude diagrams (CMDs) with the predictions of standard models. This is more than twice the age derived from fitting isochrones to low-mass stars in the CMD with the same models. Much closer agreement between LDB and CMD ages is obtained from models that incorporate magnetically suppressed convection or flux-blocking by dark, magnetic starspots. The best agreement is found at ages of 45−50 Myr for models with high levels of magnetic activity and starspot coverage fractions >50 per cent, although a uniformly high spot coverage does not match the CMD well across the full luminosity range considered.